Supply Chain Strategy for Assessing the Stock Prices of Property Sector Companies in Indonesia Stock Exchange - Sinurat, Mangasi; Erlina, Erlina; Daulay, Murni; Saputra, Jumadil; Sadalia, Isfenti; Nur Ilham, Rico (International Journal of Supply Chain Management, 2020)
The global crisis in 2008 has a tremendous impact on Indonesian economic stability. It ultimately led to increases in asset prices including property. It drives investors to invest in property companies namely stock. Thus, this study aims to examine the effect of Economic Value Added, Return on Equity, and Earnings per Share toward Stock Price. Also, the role of Price Earnings Ratio as a Moderating Variable in the relationship among variables studied. The secondary data obtained from annual reports, financial statements. The data source is the property sector companies issued on the Indonesia Stock Exchange. There are 30 companies involved in this study. The data analyzed by using the multiple linear regression analysis and moderating test applied the residual method. The results of this study indicate that partially Economic Value Added has a positive and significant effect on stock prices, Return on Equity has a negative and significant effect on stock prices, and Earning per Share has a positive and significant effect on stock prices. Variable Price Earnings Ratio does not moderate the relationship of Economic Value Added, Return on Equity and Earnings per Share to stock prices both partially and simultaneously.